Enzymatic modular assembly of hybrid Lewis antigens. Issue 37 (2nd September 2021) - Xia, Hui; Ye, Jinfeng; Cao, Hongzhi; Liu, Xianwei; Zhang, Yan; Liu, Chang-Cheng
Abstract : Facile enzymatic modular assembly of 3 complex hybrid Lewis antigens. Abstract : The enzymatic synthesis of hybrid Lewis antigens including KH-1 (Lewis y-Lewis x-Lactose, Le y -Le x -Lac), Lewis a-Lewis x-Lactose (Le a -Le x -Lac), and Lewis b-Lewis x-Lactose (Le b -Le x -Lac) has been achieved using a facile enzymatic modular assembly strategy. Starting from a readily available tetrasaccharide, 3 complex hybrid Lewis antigens were achieved in over 40% total yields in less than 5 linear steps of sequential enzymatic glycosylation using 6 enzyme modules. The regio-selective fucosylation was achieved by simply controlling the donor–acceptor ratio. This strategy provides an easy access to these biologically important complex hybrid Lewis antigens at preparative scales.